HISTORIENS PRISME - NUTIDENS HELT - Christensen, Tea Dahl (K&K - Kultur og Klasse, 2014)
THE PRISM OF HISTORY. THE HERO OF THE PRESENCE | The article presents a case of commemorative practice. The practice evolves around a historic soldier hero, Niels Kjeldsen. At the commemoration Danish soldiers, a reenactment group, a political representative and citizens participate. The case demonstrates how past and present are connected through the participants meaning-making of the commemoration. The historical soldier is used as a prism that allows the participants to commemorate and celebrate present time soldiers as potential heroes. Thereby the commemoration creates a space for acknowledging present time soldiers as potential heroes.